Joint relay selection and adaption of modulation, coding and transmit power for spectral efficiency optimisation in amplify-forward relay network - Taki, Mehrdad; Sadeghi, Mohammad (IET communications, 2014)
Three schemes are designed for joint relay selection and link adaption in amplify and forward relay network which are called RS-CAP (joint relay selection with continuous adaptation of powers), RS-DAP (joint relay selection with discrete adaptation of powers) and OTD-DAP (optimised time division with discrete adaptation of powers). In all schemes spectral efficiency is optimised using adaptive modulation, coding and transmit power subject to average power constraint of each node and a bit error rate constraint of detection. The main idea behind all designs is to save power of relays in inactive time to be utilised for active time. In RS-CAP and RS-DAP, optimised relay selection is done based on channel state information of all corresponding paths, however, in OTD-DAP just an optimised time percentage is allocated to each relay to cooperate in signal transmission. Considerable less channel estimation load is imposed on the receiver in the OTD-DAP scheme compared with the others. In RS-CAP power of nodes are continuously adapted, however, in RS-DAP and OTD-DAP, powers are discrete adaptive. Thus there is a considerable decrease in feedback rate in the RS-DAP and OTD-DAP schemes in comparison with RS-CAP. A trade-off between the performance and channel estimation load and feedback rate is seen in numerical evaluations. Noticeable improvement in achievable rates is seen by using proposed schemes compared with the previous works.